Human resource evaluation in hotel units - Aspridis, George (Management, 2012)
This paper aims at presenting and analysing the performance appraisal systems and the human potential development in hotel units. It aims at integrating and updating many aspects of performance appraisal while concentrating on the hotel units system to prove the importance of human resource evaluation in hotel units and the procedure that is to be followed by the enterprise for further development of hotel employees. HR evaluation analysis is presented through relevant theoretical background on the evaluation method and the presentation of the practical problematical issues in order to create an image for a whole evaluation system of HR in Greek hotel enterprises.
Keywords: efficiency; hoteli; hotelirstvo; kadri; management; učinkovitost; upravljanje; vodenje; zaposleni